INSTRUMENTAL MUSIC RELAXATION TO REDUCE WORK STRESS AMONG OFFICE WORKERS AT PT X - Priambodo, Prayuda Mukti; Qadrijati, Isna; Faradisha, Jihan (Kesmas Indonesia, 2025)
Work stress is a common issue among employees. One non-pharmacological method to reduce stress is instrumental music relaxation. This study aimed to evaluate the effect of a 10-minute instrumental music session, conducted over three consecutive days, on reducing work-related stress among office workers at PT X. A quasi-experimental design with a control group and pre-test–post-test measurements was employed. Sixty office workers were selected through total sampling and equally assigned to intervention and control groups. The intervention group listened to piano and nature-sound music for 10 minutes during each break for three days, while the control group received no treatment. Stress levels were measured using the Stress Diagnosis Survey (SDS) before and after the intervention. Data analysis used the Wilcoxon test for within-group comparison and the Mann–Whitney test for between-group comparison. Results showed a significant reduction in stress levels in the intervention group (p = 0.000), with 87% moving from moderate to mild stress. In contrast, the control group showed no significant change (p = 0.317). The post-test comparison between groups was also significant (p = 0.000). These findings suggest that instrumental music relaxation is an effective, low-cost intervention to improve employee mental well-being in the workplace.